2018
DOI: 10.1002/slct.201800708
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Magnetic Carbon Nanotubes Functionalized with Pyridine Groups: Synthesis, Characterization and Their Application as an Efficient Carrier for Plasmid DNA and Aptamer

Abstract: Magnetic functionalized multi‐walled carbon nanotubes have been synthesized, characterized and studied for therapeutically active nucleic acids interaction and delivery. In this study, pyridine functionalized magnetically was investigated for plasmid DNA and aptamer delivery. A thorough structural characterization of new carrierhas been carried out by means of transmission electron microscopy, scanning electron microscopy images, carbon, hydrogen and nitrogen elemental analysis, thermogravimetric analysis, vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…MWCNT functionalised with pyridine and magnetic particles transported nucleic acids bound by π-π interactions through the cell membrane and released them in the cytoplasm. A magnetic field was then applied to remove the nanocarriers from the cell, thus limiting their cytotoxicity [ 54 ]. Magnetically guided nanocarriers were also considered by Xu et al through the one-step preparation of magnetic MWCNT using a paramagnetic surfactant coating.…”
Section: Carbon Nanotubes (Cnt) For Biomedical Applicationsmentioning
confidence: 99%
“…MWCNT functionalised with pyridine and magnetic particles transported nucleic acids bound by π-π interactions through the cell membrane and released them in the cytoplasm. A magnetic field was then applied to remove the nanocarriers from the cell, thus limiting their cytotoxicity [ 54 ]. Magnetically guided nanocarriers were also considered by Xu et al through the one-step preparation of magnetic MWCNT using a paramagnetic surfactant coating.…”
Section: Carbon Nanotubes (Cnt) For Biomedical Applicationsmentioning
confidence: 99%
“…Kaboudin et al have revealed that nucleic acid can be transfected by a method other than endocytosis. MWCNTs functionalized with pyridine and magnetic particles transported nucleic acids bound by interactions over the cell membrane and into the cytoplasm [69]. The nanocarriers were subsequently removed from the cell using a magnetic field, thereby minimizing their cytotoxicity [70].…”
Section: Uses Of Cnts In Biomedicinementioning
confidence: 99%
“…Moreover, a non-viral cargo meets the criteria to qualify as a strong vector for gene therapy such as plentiful payload sum, intracellular internalization, targeted delivery and low toxicity. Scientists have utilized different types of payloads, for example, DNA, RNA, oligonucleotides (ODN), and aptamers for gene therapy along with wide tool-box of f-CNTs ( Figure 2), for the efficient delivery of biomolecules [1][2][3] into plants [44] and mammalian [42] cells. The most widely used protocol is provided by Pantarotto et al [45] where they used ammonium functionalized nanotubes (MWCNTs and SWCNTs) to form a complex with plasmid DNA (pDNA) by means of ionic bonding, which viably conveyed pDNA intracellularly.…”
Section: Conjugation Of Functionalized Carbon Nanotubes With Genes Anmentioning
confidence: 99%